2014
DOI: 10.1177/1088868314541858
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Self-Reported Attachment Styles

Abstract: For decades, attachment scholars have been investigating how parents’ adult attachment orientations relate to the ways in which they parent. Traditionally, this research has been conducted by developmental and clinical psychologists who typically employ the Adult Attachment Interview (AAI) to measure adult attachment. However, dating back to the mid-1990s, social and personality psychologists have been investigating how self-reported adult attachment styles relate to various facets of parenting. The literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
154
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(171 citation statements)
references
References 134 publications
(309 reference statements)
11
154
3
3
Order By: Relevance
“…In the present study, we focus on the association between parental attachment representations and mindful parenting and explore the mediating role of caregiving representations. Although there is compelling evidence that a secure attachment is a fundamental requirement for sensitive and responsive parental care (George & Solomon, 1999;Jones, Cassidy, & Shaver, 2015;, its association with mindful parenting has not yet been investigated.…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, we focus on the association between parental attachment representations and mindful parenting and explore the mediating role of caregiving representations. Although there is compelling evidence that a secure attachment is a fundamental requirement for sensitive and responsive parental care (George & Solomon, 1999;Jones, Cassidy, & Shaver, 2015;, its association with mindful parenting has not yet been investigated.…”
Section: Introductionmentioning
confidence: 98%
“…This result partially corroborates our hypothesis and is line with previous studies that found a significant link between avoidance and parenting stress in nonclinical populations Rholes et al, 2006) as well as between avoidance and mental health in parents of children with a congenital heart disease (Berant et al, 2001(Berant et al, , 2002(Berant et al, , 2008). Caring for a child with diabetes may be extremely stressful for parents with higher levels of avoidance because of their greater difficulty in coping effectively with stressful circumstances ) and in assuming caregiving roles (Jones et al, 2015;Rholes et al, 2006). Rholes et al (2006) argued that more avoidant parents usually experience an "approachavoidance conflict" (p. 282) because although they want to detach from others and avoid the activation of their attachment system, their parental role implies the provision of sensitive and 12 responsive care to their children.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with higher levels of avoidance have greater difficulty assuming caregiving roles Rholes et al, 2006), namely in the parenting context (Mills-Koonce et al, 2011;Jones, Cassidy, & Shaver, 2015). They are less sensitive and responsive toward their children (Jones et al, 2015;Selcuk et al, 2010), such as when teaching a new task (Rholes, Simpson, & Blakely, 1995) or during an inoculation procedure (Edelstein et al, 2004).…”
Section: Individual Differences In Parenting Stress and The Role Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…Among these maternal factors, studies have reported that postpartum depressive symptoms (PDS) might increase the risk of their progeny displaying aggression from childhood through adolescence (Barker, Copeland, Maughan, Jaffee, & Uher, 2012;Barker, Jaffee, Uher, & Maughan, 2011;Hay, Pawlby, Angold, Harold, & Sharp, 2003;O'Hara & McCabe, 2013). Potential explanations for the association between maternal PDS and childhood aggression include poor parenting styles (e.g., unsatisfactory breastfeeding and undesirable sleep practices) and maternal attachment insecurity for their infants (Field, 2010;Jones, Cassidy, & Shaver, 2015;Murray & Cooper, 1997). Therefore, it is highly possible that the children of mothers with PDS at four weeks after delivery display higher levels of aggression during early infancy.…”
Section: Introductionmentioning
confidence: 99%